Beyond Dystonia‐Parkinsonism: Chorea and Ataxia with ATP1A3 Mutations. Issue 4 (29th January 2016) - de Gusmao, Claudio M.; Dy, Marisela; Sharma, Nutan
Abstract: Mutations in the ATP1A3 gene (the α‐3 subunit of the Na + /K + ATPase) are associated with rapid‐onset dystonia‐parkinsonism; alternating hemiplegia of childhood; and cerebellar ataxia, areflexia, pes cavus, optic atrophy, and sensorineural hearing loss (CAPOS syndrome). The authors report 3 cases with pleiotropic movement disorders, including a novel mutation in a patient who presented with ataxia and dysphagia. Case 1 had a history of attention deficit hyperactivity disorder and developed dysphagia, chorea, and limb dystonia after a febrile illness at age 12 years. Case 2 presented with limb dystonia at age 26 years and dysarthia and dysphagia after a febrile illness. Case 3 had a history of learning disability and developed progressive ataxia with cerebellar atrophy at age 20 years. In all cases, deleterious mutations were identified in ATP1A3. They illustrate wide phenotypic variability, including chorea and ataxia. New cases are likely to be diagnosed as knowledge about the phenotypic spectrum expands.